Midgestational characterization of cytokine profiles in black south African pregnant women (Nigerian Journal of Physiological Sciences, 2021)
Pregnancy is thus characterized by an anti-inflammatory milieu in the second trimester despite a pro-inflammatory response in the first and third trimesters.  Nonetheless a disproportionate inflammatory response is risky in pregnancy. This retrospective study evaluated the mid-gestational expression of inflammatory and anti-inflammatory cytokines in HIV infected pregnant women at their first antenatal visit. Archived serum samples were collected from seventy (n=70) black pregnant women, attending a primary health care centre in KwaZulu-Natal, South Africa. The demographic and clinical profiles were procured from patient medical records and cytokine levels were measured in all samples. A statistical significance (p